2016
DOI: 10.1007/s13197-016-2258-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cryogenic grinding on volatile and fatty oil constituents of cumin (Cuminum cyminum L.) genotypes

Abstract: Effect of cryogenic grinding on recovery of volatile oil, fatty oil percentage and their constituents in two cumin (Cuminum cyminum L.) genotypes have been analyzed. Cryogenic grinding not only retains the volatiles but enhanced the recovery by 33.9 % in GC 4 and 43.5 % in RZ 209. A significant increase (29.9 %) over normal grinding in oil percentage was also observed in genotype RZ 209. This increase was, however, less (15.4 %) in genotype GC 4. Nineteen major compounds were identified in the essential oil of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…Cumin (Cumin cyminum), an annual herbaceous plant that belongs to the Umbelliferae family is an important component of many of the Ayurvedic decoctions (Sharma et al 2016). Cumin seeds are used as a spice for their distinctive flavor and aroma and are valued for its medicinal and therapeutic properties (Thippeswamy and Naidu 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumin (Cumin cyminum), an annual herbaceous plant that belongs to the Umbelliferae family is an important component of many of the Ayurvedic decoctions (Sharma et al 2016). Cumin seeds are used as a spice for their distinctive flavor and aroma and are valued for its medicinal and therapeutic properties (Thippeswamy and Naidu 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from spice industry, large quantities of cumin seeds are also used by Ayurvedic industries. Cumin is an important component of most of the Ayurvedic decoctions specifically used for the conditions like bloating, vomiting, diarrhea, dysentery, malabsorption syndrome, fever and skin diseases (Sharma et al 2016). Jeerakarishtam, one of the cumin based decoction, is prescribed by Ayurvedic doctors for abdominal distension, discomfort in the chest, respiratory disorders, and all digestive disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Goswami () reported that during cryogenic grinding of cloves, when temperatures decreased from −50 to −110 °C the percent retention of volatile oil increased from 13.16 to 13.31%. Similarly Sharma et al () observed that the essential oil retention of cryo‐ground cumin powder of genotype GC‐4 and RZ‐209 was increased 33.9 and 43.5% over noncryogenic grinding respectively. In addition to that, they also observed that, for different genotypes of cumin seeds, cuminaldehyde was increased significantly due to cryogenic grinding and some constituents were only recovered in cryo‐ground samples.…”
Section: Resultsmentioning
confidence: 80%
“…Lower γ‐terpinene in the volatile oil may be due to the fact that the content of cuminaldehyde, γ‐terpinene, and other components varies from variety to variety, field of growing and growing atmosphere. According to findings of Sharma et al () genotypes GC‐4 and RZ‐209 of cumin from diverse origins showed difference in essential oil constituents whether ground by either cryogenic or traditional technique. Ramezani et al () signified that the genetic constitution and environmental condition influence the yield and composition of volatile oil produced by medicinal plants.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation